miR-498 Targets UBE2T to Inhibit the Proliferation of Malignant Melanoma Cells - Wen Cao MD; Li Ni BA; Pin Li BA; Qi-Xia Wang BA; Ming-Ming Li BA; Shu-Hong Huang PhD; Ning-Ning Dang PhD (Technology in Cancer Research & Treatment)
Background: Malignant melanoma is a common malignant tumor and one of the tumors with the fastest growing incidence. The effect of microRNAs on the biological processing of malignant melanoma cells also have been reported. This study explores the ability of miR-498 to regulate the progression of malignant melanoma cells. Methods: The expression of miR-498 was detected by RT-qPCR. The proliferation, invasion, and migration of malignant melanoma cells were measured by cell counting kit-8, clone formation, and transwell assays. Flow cytometry assay detected the percentage of apoptotic cells. Western blot was used to detect the expression of markers related to epithelial–mesenchymal transition. The correction of miR-498 and UBE2T was explored by dual-luciferase assay and Western blot. Results: Overexpression of miR-498 inhibited the proliferation, invasion, migration, and induced cell apoptosis of M14 and A375 cells. In addition, the expression of epithelial–mesenchymal transition-related factors was altered by the overexpression of miR-498. miR-498 can directly target UBE2T 3'-UTR and inhibit UBE2T protein expression. The overexpression of UBE2T reversed the inhibitory effects of miR-498 on the progression of malignant melanoma cells. Furthermore, UBE2T mRNA was significantly highly expressed in malignant melanoma tissues. The high expression of UBE2T was associated with the poor overall survival rate of malignant melanoma patients. Conclusions: Altogether, our findings demonstrated that miR-498 significantly inhibited the proliferation, invasion, migration, and induced apoptosis of malignant melanoma cells and confirmed that miR-498 regulated malignant melanoma cell progression by targeting UBE2T.